An ultrashort throw ratio projection lens design based on a catadioptric structure. Issue 12 (12th July 2018) - Wang, Hsiu-Cheng; Pan, Jui-Wen
Abstract: In this paper, we present a rotational symmetry for an ultrashort throw (UST) lens with offset field. The UST lens has a throw ratio of 0.23 and a total track of 195 mm. The optical elements of the UST lens are comprised of two parts. First, a catadioptric projection lens where the catadioptric function permits reaching an ultrashort throw ratio, short total track, while at the same time requiring fewer lens elements. The second part is a collimating lens which takes advantage of the telecentric condition to generate uniform total internal reflection (TIR) in the TIR prism. With this design, an effective focal length of -1.96 mm and a f-number of 2.4 can be obtained. The root mean square spot size and lateral colour of all fields are smaller than one pixel in size. The maximum optical distortion of −0.97% and TV distortion of 0.2% are acceptable. In terms of image quality, the modulation transfer function (MTF) values for all fields are above 0.65 at 0.245 line pairs/mm. Even when the tolerance error is considered, the MTF values for all fields are still above 0.3. The suitability of the novel UST lens design for projection applications is discussed.